One-Pot Synthesis of Gold Nanoparticles on N,O-Containing Organic Group Modified Silica and Its Catalytic Performance for Selective Hydrogenation of Acetylene - Wang, Kang-Jun; Wu, Jing; Wang, Xin-Kui (Asian Journal of Chemistry, 2011)
A novel in situ autoreduction and entrapment route has been developed, by which highly dispersed gold nanoparticles could be easily prepared on modified silica in one step. The aminopropyl groups were introduced onto silica via sol-gel condensation of tetraethoxylsilicate (TEOS) and aminopropyltriethoxysilane (APTES). The formaldehyde can be anchored on amino groups to form N,O-containing organic groups (NHCH2OH). The resulted N,O-containing organic groups can directly reduce the HAuCl4 to form highly dispersed gold nanoparticles on modified silica at room temperature. The as-synthesized novel gold catalyst, compared with gold supported on commercial silica prepared by conventional deposition-precipitation method, showed much better stability, activity and selectivity for selective acetylene hydrogenation.